Unusual catalytic properties of high-energetic-facet polar metal oxides - Li, Y; Tsang, SCE (American Chemical Society, 2020)
Conspectus Heterogeneous catalysis is an area of great importance not only in chemical industries but also in energy conversion and environmental technologies. It is well-established that the specific surface morphology and structure of solid catalysts exert remarkable effects on catalytic performances, since most physical and chemical processes take place on the surface during catalytic reactions. Different from the widely studied faceted metallic nanoparticles, metal oxides give more complicated structures and surface features. Great progress has been achieved in controlling the shape and exposed facets of transition metal oxides during nanocrystal growth, usually by using surface-directing agents (SDAs). However, the effects of exposed facets remain controversial among researchers. It should be noted that high-energetic facets, especially polar facets, tend to lower their surface energy via different relaxation processes, such as surface reconstruction, redox change, adsorption of countercharged species, etc. These processes can subsequently lead to surface defect formation and break the surface stoichiometry, and the resulting changes in electronic configurations and charge migration properties all play important roles in heterogeneous catalysis. Because different materials prefer different relaxation methods, various surface features are created, and different techniques are required to investigate the different features from facet to facet. Conventional characterization techniques such as X-ray diffraction, X-ray photoelectron spectroscopy, transmission electron microscopy, etc. appear to be insufficient to elucidate the underlying principles of the facet effects. Consequently, an increasing number of novel techniques have been developed to differentiate the surface features, enabling greater understanding of the effects of facets on heterogeneous catalysis.